Cooperative Prototyping: Users and Designers in Mutual Activity - Bødker, Susanne; Grønbæk, Kaj (DAIMI Report Series, 1990)
In most development projects, descriptions and prototypes are developed by system designers on their own, utilizing users as suppliers of information on the use domain. In contrast, we are proposing a cooperative prototyping approach where users are involved actively and creatively in design and evaluation of early prototypes. This paper illustrates the approach by describing the design of computer support for casework in a technical department of a Danish municipality. Prototyping is viewed as an on-going learning process, and we analyze situations where openings for learning occur in the prototyping activity. The situations seem to fall into four categories: 1) Situations where the future work situation with a new computer application is simulated to some extent to investigate the future work activity. 2) Situations where the prototype is manipulated and used as a basis for idea exploration. 3) Situations focusing on the designers' learning about the users' work in practice. 4) Situations where the prototyping tool or the design session as such becomes the focus. Lessons learned from the analysis of these situations are discussed. In particular we discuss a tension between the need for careful preparation of prototyping sessions and the need to establish conditions for user and designer creativity. Our conclusion is that users and designers should prepare to learn from breakdowns and focus shifts in cooperative prototyping sessions rather than they should try to avoid them.